Root instrumentation with an erbium : yttrium-aluminum-garnet laser: Effect on the morphology of fibroblasts - Rossa, C.; Silverio, K. G.; Zanin, ICJ; Brugnera, A.; Sampaio, JEC (Quintessence Publishing Co Inc, 2002)
Objective: the purpose of this study was to evaluate the effect of erbium:yttrium-aluminum-garnet laser instrumentation of root surfaces on the morphology of fibroblasts from continuous lineage. Method and materials: Dentinal slices with 4 mm(2) of surface area were obtained from teeth extracted for severe periodontal involvement. Specimens were assigned to one of three treatment groups: group 1, application of the laser with an energy level of 250 mJ at 103 pulses per second; group 2, application of the laser with an energy level of 80 mJ at 166 pulses per second; and group 3, similar to group 2, but with concomitant water irrigation of the device. The specimens were incubated in multiwell plates containing cell culture media. After 24 hours, the specimens were submitted to routine preparation for scanning electron microscopy. Three independent and blind examiners used photomicrographs to evaluate the morphology of the fibroblasts: 0 = without cells; 1 = flat cells; 2 = round cells; and 3 = combination of round and flat cells. Results: Statistical analysis indicated that there were significant differences among treatment groups and that group 3 was significantly different from groups 1 and 2. Conclusion: There was no difference between groups 1 and 2 in the morphology of fibroblasts. Laser instrumentation with concomitant irrigation impaired the adhesion of fibroblasts to dentinal surfaces.
Keywords: fibroblast; laser; periodontal disease; periodontal therapy; tooth root